Toward a new paradigm for growth modeling in fisheries stock assessments: Embracing plasticity and its consequences - Lorenzen, Kai (Fisheries research, 2016)
•Body growth is a central process in fish population dynamics and fisheries assessment.•Fish growth is phenotypically plastic, responding to environmental conditions including food availability.•Plasticity in growth can have important implications for fisheries assessment and management. Modeling of body growth forms an essential part of many fisheries stock assessments. Growth influences population dynamics through its effects on lifetime patterns of biomass production, natural and fishing mortality, and reproductive output. By relating size to age, growth models also enable the use of size-based data in age-based stock assessments. Growth patterns are commonly assumed to be constant (time-invariant) or at best subject to inconsequential process noise. However, fish growth is inherently plastic, often responding strongly to environmental conditions such as temperature and food availability. In wild fish stocks, this results in median temporal variation of around 15% in length-at-age and 40% in weight-at-age, with extremes of 20% (length) and 60% (weight). Plasticity mediates environmental forcing and density-dependence in growth, both of which can have important implications for stock assessment and management. Failing to account for such effects can lead to substantial deviations (often more than 30%) in reconstructed stock dynamics, projections and reference points. The nature and magnitude of such deviations depends not only on the statistical adequacy of the growth model but on how growth information is used in the stock assessment process and on the management options being evaluated. In addition to having direct assessment and management consequences, plasticity provides a unified conceptual framework for interpreting various disparate and at times, confusing patterns of fish growth. Therefore, I conclude that the “constant growth” paradigm of fisheries stock assessments should be replaced with a paradigm that embraces growth plasticity and its consequences.